Pertumbuhan Setek Buah Naga Merah (Hylocereus polyrhizus) Pada Berbagai Konsentrasi Benzylamino Purine Media Tanam Berbeda - Fadlia Wahyuni; Fathurrahman Fathurrahman; Muhardi Hasanuddin (Mitra Sains, 2018)
This study aims to determine the effect of plant growth regulator in this case is the BAP and the influence of the planting medium composition on the growth of dragon fruit cuttings. This study was designed in a randomized block design with two factors, namely the concentration of BAP treatment and growing media. BAP concentration tested BAP consisting of 0 ppm, 25 ppm, 30 ppm and 35 ppm, while the planting medium used rice husk + soil + manure (cow, chicken, goat), then gained 12 combined treatment. Each combination treatment was repeated 3 times so that there are 36 experimental units. Each treatment was made four cuttings, so the total number of cuttings used is 144 dragon fruit cuttings. The results showed that the growth of the dragon fruit is strongly influenced by the concentration of BAP and planting medium used. Shoot height and dry weight of stem was obtained at a concentration of 35 ppm BAP using goat and cow manure. In the treatment of high shoots reaching an average of 33.90 cm and a dry weight rod 347.53. Number of shoot, root length and root volume were both acquired in the media rice husk + soil + chicken manure. In such treatment the amount of 2.771 bud bud, root length of 31.40 cm, and a volume of 70.00 root strands. The dry weight of the roots of the nicest obtained on media rice husk + soil + cattle manure. In the treatment of root dry weight 2.11 strands.